Hubungan Pengetahuan dan Sikap dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Laubaleng, Kecamatan Laubaleng, Kabupaten Karo Tahun 2023 - Erlista Ginting; Siska Suci Triana Ginting; Febri Panjaitan; Roswita Roswita (NAJ Nursing Applied Journal, 2024)
Anemia is a condition in which the body has too few red blood cells (erythrocytes) which contain hemoglobin which functions to carry oxygen to all body tissues. Signs and symptoms of anemia include fatigue, weakness, decreased capacity/ability or work productivity. Anemia in pregnancy is a condition in which the mother has Hb levels below 11 gr% in the first and second trimesters or levels <10.5 gr% in the third trimester (Proverawati, 2016). One of the biggest health problems suffered by pregnant women in the world is anemia because it is a direct cause of death. Globally, the prevalence of anemia suffered by people around the world is 2.3 billion. Around 50% of it is caused by iron deficiency anemia (World Health Organization (WHO, 2017). The type of research used in this study is analytical with a cross-sectional approach. Cross-sectional is a research approach that emphasizes the time of measurement/observation of independent and dependent variable data only once at one time. This study was conducted to determine the relationship between one variable and another. (Notoatmodjo, 2018)